Brown Dog novellas - Harrison, Jim 1937-2016 (Grove, 2013)
"Of all [Jim Harrison's] creations, Brown Dog has earned cult status with readers in the more than two decades since his first appearance, scrambling to stay out of jail after his salvage-diving operation uncovers the frozen body of an Indian man in the waters of Lake Superior. Now, for the first time, this book gathers all the Brown Dog novellas, including one never before published, into one volume"--Jacket